Activity-aware essential tremor evaluation using deep learning method based on acceleration data - Zheng, Xiaochen; Vieira, Alba; Marcos, Sergio Labrador; Aladro, Yolanda; Ordieres-Meré, Joaquín (Parkinsonism & related disorders, 2019)
Essential tremor (ET), one of the most common neurological disorders is typically evaluated with validated rating scales which only provide a subjective assessment during a clinical visit, underestimating the fluctuations tremor during different daily activities. Motion sensors have shown favorable performances in both quantifying tremor and voluntary human activity recognition (HAR). To create an automated system of a reference scale using motion sensors supported by deep learning algorithms to accurately rate ET severity during voluntary activities, and to propose an IOTA based blockchain application to share anonymously tremor data. A smartwatch-based tremor monitoring system was used to collect motion data from 20 subjects while they were doing standard tasks. Two neurologists rated ET by Fahn-Tolosa Marin Tremor Rating Scale (FTMTRS). Supported by deep learning techniques, activity classification models (ACMs) and tremor evaluation models (TEMs) were created and algorithms were implemented, to distinguish voluntary human activities and evaluate tremor severity respectively. A practical application example showed that the proposed ACMs can classify six typical activities with high accuracy (89.73%–98.84%) and the results produced by the TEMs are significantly correlated with the FTMTRS ratings of two neurologists (r1 = 0.92, p1 = 0.008; r2 = 0.93, p2 = 0.007). This study demonstrated that motion sensor data, supported by deep learning algorithms, can be used to classify human activities and evaluate essential tremor severity during different activities. •An automatized system to score Essential Tremor is presented.•It classifies the tremor level, but also it automatically identifies the action done.•Accuracy in classification of activities is over 89%.•High degree of correlation (>90%) with two neurologists for scoring of the tremor.•An anonymized exchange of patients' data based on blockchain IOTA is presented.